The Potential Impacts of Invasive Quagga and Zebra Mussels on Macroinvertebrate Communities: An Artificial Stone Substrate Based Field Experiment Using Stable Isotopes - Zhang, Hui; Yohannes, Elizabeth; Rothhaupt, Karl-Otto (Frontiers in Ecology and Evolution, 2022)
Over the past decades, zebra mussel (Dreissena polymorpha) and quagga mussel (D. rostriformis bugensis) invaded multiple freshwater systems and posed major threat to the overall ecosystem. In Lake Constance where zebra mussels invaded in 1960s, the quagga mussel invasion progressed at a very high rate since 2016, providing an opportunity to study the ecological impact of both species at an early stage. We conducted a field experiment in the littoral region of the lake using standardized stone-substrates, which were blank, glued with empty shells of mussels, with living adult quagga mussels and with living adult zebra mussels to monitor the differences in colonization of macroinvertebrate community. Empty shells and the shells of both living adult quagga and zebra mussels created more colonization areas for newly settled macroinvertebrates. The abundance of newly settled quagga mussels was higher than zebra mussels, indicating the outcompeting behavior of quagga mussels. We used stable isotopes (δ13C and δ15N) of both dreissenids, and their potential competitors, which include two snail species (New Zealand mud snail Potamopyrgus antipodarum, common bithynia Bithynia tentaculate) and additional invasive gammarid species (killer shrimp Dikerogammarus villosus), in order to investigate their feeding ecology and to evaluate their potential impacts on macoinvertebrate community structure and interactions. The δ13C and δ15N of neither the newly settled quagga mussels nor the well-established zebra mussels differed significantly among various treatments. Newly settled quagga mussels had higher δ13C values than newly settled zebra mussels and showed similar differences in all four stone set-ups. During the experiment period (with quagga and zebra mussels still coexisting in some regions), these two dreissenids exhibited clear dietary (isotopic) niche segregation. The rapid expansion of invasive quagga mussel coupled to the higher mortality rate of zebra mussels might have caused a dominance shift from zebra to quagga mussels. The study offers the first overview of quagga mussel’s progressive invasion and the reaction of zebra mussels and other newly settled macroinvertebrates, and compliments to the hypothesis of facilitative associations of invasive dreissenids. Results provide an experimental benchmark by which future changes in trophic ecology and invasion dynamics can be measured across the ecosystem.